Current practices for diagnosis and management of Canine Cognitive Dysfunction Syndrome in the United States - Simon, Katherine E.; Gruen, Margaret E.; Olby, Natasha J. (Frontiers in Veterinary Science, 2025)
IntroductionThere are currently no accepted guidelines for the diagnosis and management of Canine Cognitive Dysfunction Syndrome (CCDS). The objective of this study was to describe the current diagnostic and management practices regarding CCDS by veterinarians in the United States (US).MethodsAn anonymous online survey was distributed to veterinary practitioners from January to May 2025. The survey included questions regarding patient population, CCDS diagnosis and treatment and client interactions.ResultsA total of 318 survey responses were obtained from veterinarians who saw companion dogs regularly. Nearly all (97.2%) had made a diagnosis of CCDS in their career, citing patient history and clinical signs/ behavioral changes as the tools they use to make a diagnosis. Most veterinarians (approximately 80%) rarely or never referred their potential CCDS cases to a veterinary specialist. When managing their CCDS patients, pharmaceuticals are most often recommended, specifically selegiline. Selegilline was also considered most effective in managing CCDS, however this view was held by only about 30% of veterinarians. Responses reflected uncertainty regarding best practices and treatment efficacies, with veterinarians citing lack of knowledge and owner-related barriers such as lack of interest or financial constraints as factors which hinder treatment recommendations.DiscussionResults from this survey underscore there are still significant gaps in knowledge as to best practices for the diagnosis and management of CCDS. Clear CCDS diagnostic and management guidelines are needed to support veterinarians and address the therapeutic needs of patients.